The Concept of Aesthetic Value in the Lvov-Warsaw School: An Overview - Horecka, Aleksandra (Filozofia Nauki, 2022)
This article discusses selected conceptions of aesthetic value formulated by representatives of the Lvov-Warsaw School, including Kazimierz Twardowski, Władysław Witwicki, Władysław Tatarkiewicz, Tadeusz Czeżowski, Mieczysław Walfisz-Wallis, Stanisław Ossowski, Leopold Blaustein, and Tadeusz Kotarbiński.